The Prosody of Directive Speech Acts: Pragmastylistic Aspect (On the Material of the Modern German Language) - Karandeeva, L.G.; Stanchuliak, T.G.; Popova, S.V.; Suyskaya, V.S.; Shvedova, I.V. (International Journal of Criminology and Sociology, 2022)
The article represents the results of a phonetic experiment devoted to the study of pragmatically, and the stylistically determined manifestation of directive speech acts in the modern German language. The experiment allowed establishing the prosodic invariant of the directive speech act and describing variant patterns realized in diverse situational conditions which demonstrated a different degree of categoricalness and revealed their differential character on the level of prosodic expressive means. The research showed that pragmatic identification and stylistic differentiation of directive speech acts is realized utilizing all prosodic parameters - pitch, intensity and tempo. The complex analysis of pitch, intensity and tempo characteristics specific for situational variants of the directive illocutive allowed defining the level of involvement of these prosodic means in the functional realization of directive speech impact.